Ranking Suicidal Comments on Reddit - Hurtado Cruz, Aron Josue (2024)
The project focuses on the development of a Natural Language Processing (NLP) algorithm designed to detect suicidal comments on the Reddit platform and subsequently perform a negative sentiment analysis for the purpose of providing support to users who may be at risk of suicide. To achieve this goal, the project combines concepts and techniques from artificial intelligence, natural language processing and psychology/psychiatry. To evaluate the efficiency of the project we applied the F1 metric obtaining a fairly acceptable result with respect to a textual classification.